PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 004 DUSUN TUA KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Merry Yuhelmita; Eddy Noviana; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to improve learning outcomes IPS class IV SDN 004 Dusun Tua Kecamatan Kelayang Kabupaten Indragiri Hulu through the implementation of cooperative learning model Group Investigation. The hypothesis in this study is that if implemented GI cooperative learning model, it can improve student learning outcomes IPS. This type of research is qualitative research, namely in the form of classroom action research (Classroom Actions Research). The subject is the fourth grade students of SDN 004 Dusun Tua totaling 20 students consisting of 13 boys and 7 girls. Based on the results of research and data analysis known that an increase in students' results seen from the Learning IPS before being applied cooperative learning model GI is 63. Students who completed 7 people (35%) of 20 students. In the first cycle UH 1 daily value increased to 68.25 students who have increased as much as 8.33% by the number of students who completed 13 students from 20 students (65%). At UH 2 increased learning outcomes as much as 17,21% to 80. All the students completed the implementation of the UH 2, the classical completeness of all students completed to 100%. The increase was supported by the activities of teachers in the first cycle of success earned an average of 72.92% with good criterion. In the second cycle average of  91.67% success with the criteria very well. As for the activity of the first cycle siswauntuk batting average 64.58% with sufficient criteria. In the second cycle the average success 89.58% with good criterion. It can be concluded that cooperative learning model of Group Investigation (GI) can improve learning outcomes IPS class IV SDN 004 Dusun Tua Kecamatan Kelayang Kabupaten Indragiri Hulu. Keywords: Cooperative Learning Model GI, IPS Learning Outcomes